Investigate the Feasibility of Repurposing Existing Drugs or Identifying Novel Compounds for Diabetes Management Through Computational Docking (Journal of Advances and Scholarly Researches in Allied Education, 2024)
One way to manage type 2 diabetes mellitus, a long-term health issue, is to reduce the pace at which carbohydrates are broken down in the body. This may be achieved by blocking the enzyme α-glucosidase. There is a fast rise in the number of instances of type 2 diabetes, and there are currently no effective, safe, or widely used medications to treat it. The research aimed to examine the molecular processes and intended to use medications licensed by the food and drug administration (FDA) against α-glucosidase in drug repurposing. The possible inhibitor against α-glucosidase was identified by refining and optimizing the target protein by adding missing residues and minimizing to reduce conflicts. Following the docking investigation, the most effective compounds were chosen to create a pharmacophore query. This query will be used for the virtual screening of FDA-approved medicinal molecules that have comparable shapes. Based on binding affinities (−8.8 kcal/mol and −8.6 kcal/mol) and root-mean-square-deviation (RMSD) values (0.4 Å and 0.6 Å), the study was carried out using Autodock Vina (ADV). In order to learn about the receptor-ligand specific interactions and stability, two of the most powerful lead compounds were chosen for a molecular dynamics (MD) simulation. In comparison to conventional inhibitors, the docking score, RMSD values, pharmacophore studies, and MD simulations demonstrated that two compounds, namely Trabectedin (ZINC000150338708) and Demeclocycline (ZINC000100036924), had the ability to inhibit α-glucosidase. These projections demonstrated that the drugs Demeclocycline and Trabectedin, which have been authorized by the FDA, might be repurposed to fight type 2 diabetes.